Roles of Estrogen, Estrogen Receptors, and Estrogen-Related Receptors in Skeletal Muscle: Regulation of Mitochondrial Function - Yoh, Kenta; Ikeda, Kazuhiro; Horie, Kuniko; Inoue, Satoshi (International journal of molecular sciences, 2023)
Estrogen is an essential sex steroid hormone that functions primarily in female reproductive system, as well as in a variety of tissues and organs with pleiotropic effects, such as in cardiovascular, nervous, immune, and musculoskeletal systems. Women with low estrogen, as exemplified by those in postmenopause, are therefore prone to suffer from various disorders, i.e., cardiovascular disease, dementia, metabolic syndrome, osteoporosis, sarcopenia, frailty, and so on. Estrogen regulates the expression of its target genes by binding to its cognate receptors, estrogen receptors (ERs) α and β. Notably, the estrogen-related receptors (ERRs) α, β, and γ are originally identified as orphan receptors that share substantial structural homology and common transcriptional targets with ERs. Accumulating evidence suggests that ERs and ERRs play crucial roles in skeletal muscles, such as muscle mass maintenance, muscle exercise physiology, and muscle regeneration. In this article, we review potential regulatory roles of ERs and ERRs in muscle physiology, particularly with regard to mitochondrial function and metabolism.